2004
DOI: 10.1007/s00268-004-7603-1
|View full text |Cite
|
Sign up to set email alerts
|

131I‐Meta‐iodobenzylguanidine in the Management of Metastatic Midgut Carcinoid Tumors

Abstract: The management of metastatic neuroendocrine tumors incorporates multimodal therapy with surgery, biotherapy, and chemotherapy. Tumor-targeted therapies using radiolabeled octreotide and metaiodobenzylguanidine (mIBG) represent a novel treatment approach. The aim of this study was to evaluate the effectiveness of 131I-mIBG in the treatment of metastatic midgut carcinoid tumors. survival outcomes were assessed for patients treated at two regional cancer centers and then compared. One center used 131I-mIBG routin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
23
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 37 publications
7
23
0
Order By: Relevance
“…The proportion of patients experiencing symptomatic benefit from 131 I-MIBG therapy (56.3%) was similar to that reported in previous studies (Safford et al, 2004;Sywak et al, 2004). As in one previous similar study (Safford et al, 2004), survival after 131 I-MIBG therapy was best predicted by a subjective symptomatic response to treatment.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The proportion of patients experiencing symptomatic benefit from 131 I-MIBG therapy (56.3%) was similar to that reported in previous studies (Safford et al, 2004;Sywak et al, 2004). As in one previous similar study (Safford et al, 2004), survival after 131 I-MIBG therapy was best predicted by a subjective symptomatic response to treatment.…”
Section: Discussionsupporting
confidence: 87%
“…It is thought that emission of ionising radiation at this site results in tumour decay (Mukherjee et al, 2001;Rose et al, 2003;Pasieka et al, 2004). This therapy has been used to treat NETs of various types, including gastroenteropancreatic NETs (Pathirana et al, 2001;Pasieka et al, 2004;Safford et al, 2004;Sywak et al, 2004;Buscombe et al, 2005), paraglangliomas (Mukherjee et al, 2001;Safford et al, 2003;Fitzgerald et al, 2006), phaeochromocytomas (Castellani et al, 2000;Rose et al, 2003;Safford et al, 2004;Fitzgerald et al, 2006), medullary carcinoma of the thyroid (Castellani et al, 2000(Castellani et al, , 2003Mukherjee et al, 2001) and neuroblastomas (Howard et al, 2005;Matthay et al, 2007). A number of previous studies had demonstrated significant symptomatic benefit in 40 -60% of patients with metastatic NETs following 131 I-MIBG therapy (Safford et al, 2004;Sywak et al, 2004), in a safe and cost-effective manner (Pathirana et al, 2001).…”
mentioning
confidence: 99%
“…Interestingly, Sywak et al compared two groups of patients with midgut NETs. 36 The first group (n=58) was treated in a centre where 131 I-MIBG was available while the second group (n=59) had no access to 131 I-MIBG (or other radio-targeted treatments). The 5-year survival rate in the first group was 63% versus 47% in the second group (p=0.1)…”
Section: Mibg Imaging and Therapymentioning
confidence: 99%
“…Such therapy makes use of specific cellular structures, the reuptake mechanism, and storage granules in specialized neuroendocrine cells to target and concentrate within tumor cells (7,8). Since their introduction into routine clinical practice in the 1980s, most reported 131 I-MIBG treatment protocols have comprised therapeutic activities between 3.7 and 11.1 GBq (100 and 300 mCi, respectively) per course (9,10). Some centers use body weight-adapted schedules, such as 92.5 MBq/kg (2.5 mCi/kg) (9,10).…”
mentioning
confidence: 99%
“…Since their introduction into routine clinical practice in the 1980s, most reported 131 I-MIBG treatment protocols have comprised therapeutic activities between 3.7 and 11.1 GBq (100 and 300 mCi, respectively) per course (9,10). Some centers use body weight-adapted schedules, such as 92.5 MBq/kg (2.5 mCi/kg) (9,10). In more recently introduced dose-intensified schedules, activities of 14.8-18.5 GBq (400-500 mCi) per treatment course were used; high-dose schedules might incorporate more than 22.2 GBq (600 mCi) supported by potential autologous stem cell rescue (11,12).…”
mentioning
confidence: 99%